Impact of Cloud Computing for Engaging Customers with the Consideration of Business Success - Himani R. Gandhi; Dr. Bhawesh Kumawat (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Cloud computing has emerged as a transformative technology, reshaping how businesses operate and engage with customers. This study examines the impact of cloud computing on customer engagement and business success, with a focus on adoption levels, perceived benefits, and customer interaction enhancements. The research analyzes the socio-demographic profile of respondents to identify significant differences in perception regarding cloud-based services. Using statistical tools such as Chi-Square tests, the study evaluates the relationship between demographic factors i.e. gender, age, and education and key cloud computing factors. The findings indicated that while businesses recognize the benefits of cloud computing such as cost savings, scalability, and improved efficiency. There are notable differences in perception across demographic groups. The study also highlights that cloud solutions significantly enhance customer engagement, leading to improved satisfaction and brand loyalty. However, challenges remain in maximizing cloud adoption and addressing security concerns. The research concluded that businesses must adopt strategic approaches to cloud integration, considering demographic variations to optimize its impact on engagement and overall business success.